Carved Stambhas (buttresses) on the walls of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the jangha (wall) of the Undeshwar Temple exhibits carved stambhas (buttresses) positioned between the bhadras (central offsets). Each side features five buttresses, with the central one depicting the dikapalas (deities of cardinal directions), while the others portray female dancers, musicians, surasundaris (celestial damsels), and alasa kanya (a form of indolent female or maiden).